ANALISIS NON PERFORNING LOAN (KREDIT BERMASALAH) TERHADAP PEMBERIAN KREDIT PADA BANK SULAWESI TENGGARA (SULTRA) - SARI, Murni (Business UHO: Jurnal Administrasi Bisnis, 2016)
Bank as a finanacial institution that has a function as financial intermediation. One function of financial intermediation is funneling credit to the community. The various problems faced by the Bank with regard to channelling credit. The increasing channelling of credit, usually accompanied with an increase in bad debt or bad credit on credit given. Bad debt in the Banking terms called the Non Performing loan (NPL) for it, the need for policy in the granting of appropriate credit to overcome the existing problems. This research was conducted to find out the Non Performing Loan on granting credit is applied to the Bank in southeast sulawesi in 2011-2015, using the principles in accordance with policy gift credit Bank Indonesia related to the eligibility of the client in the obtaining credit. The data used in this research is the primary and secondary data. Primary data obtaineby conducting interviews and direct observation and related credit division. While secondary data obtained from studies of the literature and data obtained from company in the form of the annual report, an analisys of descriptive analisys is used. The period of observation shows that the Non Performing Loan is applied to Bank have good enough South East Sulawesi in accordance wiyh existing theories because it has been applying the principle of prudence and the policy gift credit in the granting of credit in accordance with Banking policy related to the channeling of credit. Key words: The Non Performing Loan, Credit Granting Policies